2006
DOI: 10.1111/j.1360-0443.2006.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Viewing videotape of themselves while experiencing delirium tremens could reduce the relapse rate in alcohol‐dependent patients

Abstract: Videotape exposure in delirium tremens is an original therapeutic method which seems to be effective in reducing relapse risk in patients with alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Participants stated that their coping behaviour during PBC closely resembled their coping behaviour during other daily life activities, and we continued to use PBC as a point of reference when exploring how these participants coped with breathlessness during daily living. According to the video literature (Davidoff et al, 1998;Horwitz et al, 2003;Mihai et al, 2007), people viewing themselves stimulate their memory and narration. Therefore, using video for self-observation is pivotal in VN, and it was used to stimulate the participants' memory supporting their narration regarding what it is like to live with chronic breathing difficulties.…”
Section: Data Collectionmentioning
confidence: 99%
“…Participants stated that their coping behaviour during PBC closely resembled their coping behaviour during other daily life activities, and we continued to use PBC as a point of reference when exploring how these participants coped with breathlessness during daily living. According to the video literature (Davidoff et al, 1998;Horwitz et al, 2003;Mihai et al, 2007), people viewing themselves stimulate their memory and narration. Therefore, using video for self-observation is pivotal in VN, and it was used to stimulate the participants' memory supporting their narration regarding what it is like to live with chronic breathing difficulties.…”
Section: Data Collectionmentioning
confidence: 99%
“…Excluded were studies that did not use adult substance users or did not have follow-ups after 6 months or before 2 years. Although the mean, median, and modal completion rates all were 73%, rates ranged widely from 43% to 100% (Bacharach et al, 2007;Burke and Gregoire, 2007;Davey et al, 2007;Freyer et al, 2007;Fridell et al, 2007;Gossop et al, 2007;Jason et al, 2007;Matzger and Weisner, 2007;Mensinger et al, 2007;Mihai et al, 2007;Moggi et al, 2007;Niv and Hser, 2007;Robinson et al, 2007;Wade et al, 2007;Williams et al, 2007;Williamson et al, 2007). It is worth noting, …a response rate in excess of 85% is viewed as an excellent rate of return.…”
mentioning
confidence: 98%
“…Mihai et al (2006) for example found that alcohol-dependent individuals that retrospectively viewed recordings of their own delirium tremens were less likely to suffer relapse than those that did not see such videos. Mihai et al argue that the use of video in such a manner provided some therapeutic value in the treatment of dependency due to the collaborative and informative application of the method.…”
Section: Visual Methods: Documentary Documentation and Substance Usementioning
confidence: 96%